Cyclization Strategies for the Concurrent Installation of Multiple Quaternary Stereogenic Centers. Issue 7 (16th May 2021) - Alachouzos, Georgios; Frontier, Alison J.
Abstract: In this review we highlight the general cyclization strategies currently available to organic chemists for the concurrent and stereoselective installation of multiple Quaternary Stereogenic Centers (QSC) atoms in cyclic or polycyclic architectures. QSCs embedded in rigid cyclic architectures are motifs found in many blockbuster drugs and important bioactive natural product classes, and yet, direct access to these structures stereoselectively from simple precursors remains a significant challenge. Underscoring the difficulty associated with their synthesis, such topologically three‐dimensional molecules are underrepresented in existing small molecule compound libraries, which are instead dominated by linear or flat molecules. This review focuses on methods disclosed in both natural product synthesis and methodology studies since the turn of the 21 st century. The cases to be examined successfully achieve these challenging transformations: (1) one‐step assembly of the cyclized architecture ; and (2) concurrent stereoselective installation of multiple (≥2) new QSCs . These cyclization strategies, which address the aforementioned fundamental challenges in complex molecule synthesis, have been categorized into five broad groups: i) Biomimetic Polyene Cyclization Cascades; ii) Cyclization Cascades of Prochiral Alkenes; iii) Cycloadditions; iv) Dearomatizations; v) Electrocyclizations. Abstract :